Why Australia needs a sustainable population policy - Howat, Peter; Stoneham, Melissa (Australian Council for Educational Research, 2010)
Australia urgently needs to develop a sustainable population policy. There is strong evidence that if we let our population keep growing as fast as it is doing now (about 2% a year) our quality of life in Australia is likely to decline.